Analytical Hierarchy Process (AHP), Economic Order Quantity (EOQ), and Reorder Point (ROP) in Inventory Management System - Adrian Dicky Lukiman; Richard Richard (Bina Nusantara University, 2020)
The research discussed the design of vendor selection features using the Analytical Hierarchy Process (AHP) method, inventory control using Economic Order Quantity (EOQ) method, and order notification using Reorder Point (ROP) method. The research aimed to find out the most appropriate time for procurement of goods, selection of vendors that fit the predetermined criteria and determine the number of items that had to be ordered within a period of time. Object-Oriented Analysis and Design (OOAD) method was used in building the system design. The sample of the research was a telecommunications service provider company. The result shows that by applying these three methods, the problems are overcome.